PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (K3) MENGGUNAKAN METODE HIRA DAN FTA (Studi Kasus Proyek Gedung SDN Sendangharjo 4 Tuban) - Eko wahyu abryandoko dan Mushthofa (Universitas Bojonegoro, 2018)
Occupational Safety and Health is the most important part of the company especially in construction work. This study establishes a procedure based on observations with reference to HIRA and FTA approaches that occur to workers in the work. This study aims to determine the level of risk and potential hazards in construction project work and the most potential category in project work. This research is expected to follow up the biggest cause factor that happened to worker in project work of SDN Sendangharjo 4 Tuban.